The effects of sodium bicarbonate ingestion on cycling performance and acid base balance recovery in acute normobaric hypoxia - Gough, L. A.; Deb, S. K.; Brown, D.; Sparks, A.; McNaughton, L. R. (Journal of Sports Sciences, 2019)
This study investigated the effects of two separate doses of sodium bicarbonate (NaHCO3) on 4 km time trial (TT) cycling performance and post-exercise acid base balance recovery in hypoxia. Fourteen club-level cyclists completed four cycling TT`s, followed by a 40 min passive recovery in normobaric hypoxic conditions (FiO2 = 14.5%) following one of either: two doses of NaHCO3 (0.2 g/kg BM; SBC2, or 0.3 g/kg BM; SBC3), a taste-matched placebo (0.07 g/kg BM sodium chloride; PLA), or a control trial in a double-blind, randomized, repeated-measures and crossover design study. Compared to PLA, TT performance was improved following SBC2 (p = 0.04, g = 0.16, very likely beneficial), but was improved to a greater extent following SBC3 (p = 0.01, g = 0.24, very likely beneficial). Furthermore, a likely benefit of ingesting SBC3 over SBC2 was observed (p = 0.13, g = 0.10), although there was a large inter-individual variation. Both SBC treatments achieved full recovery within 40 min, which was not observed in either PLA or CON following the TT. In conclusion, NaHCO3 improves 4 km TT performance and acid base balance recovery in acute moderate hypoxic conditions, however the optimal dose warrants an individual approach.